Pemberdayaan Perempuan Buta Huruf Melalui Program Literasi Muslimat NU Di Desa Sugihwaras - miftahus sa'adah (IAIN Padangsidimpuan, 2022)
Empowerment is a development effort by giving strength to weak parties to be able to identify and build themselves. In the village of Sugihwaras itself, the weak side are women who are still illiterate. Women in Sugihwaras Village have retardation in terms of reading, even though there have been efforts from the government to overcome them. The purpose of this study was to find out about the empowerment of women who are still illiterate in Sugihwaras Village through a program from NU Muslimat. This study uses a qualitative method. The results showed that the number of illiterate women encouraged the NU Ranting Sugihwaras organization to hold women's empowerment programs such as special schools for mothers. The program is expected to improve literacy culture so that it can advance women and development in Sugihwaras Village.